Perancangan Aplikasi Android untuk Kegiatan Tahfizh Alquran Daring menggunakan Platform Firebase - Abdullah Ardi (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2021)
Tahfizh Al-quran is a form of religious activity that has the meaning of preserving and maintaining the Al-quran, so that counterfeiting and alteration activities do not occur and can guard against forgetfulness, either in whole or in part. The current problem with the pandemic condition has made some students and even the community maintain a distance in carrying out their daily activities, especially the Al-Quran memorization activities carried out by MTT Miftahul Janah. This aspect causes all forms of activities to be carried out online considering that the activities of Tahfiz Al-Quran activities must continue to run, on the other hand this problem makes it unscheduled and well documented for all forms of Al-Quran memorization activities. The purpose of making this application is so that students and the public as well as tutors can monitor all Tahfizh Alquran activities on MTT Miftahul Janah run without obstacles, are scheduled and documented. This application was developed by applying a process model with an iterative process flow, namely an iterative / incremental model. In the waterfall model, each development process is carried out sequentially, starting from communication, planning, modeling, construction to deployment, so that the next iteration will be carried out after the previous iteration is complete or in conjunction with the previous iteration. The result was a prototype of a mobile-based Android application system with the firebase platform to support the activities of Tahfizh Al-quran at MTT Miftahul Janah.